Various Passive Filter Designs Proposed for Harmonic Extenuation in Industrial Distribution Systems - Junesco, Devan; Al-Youif, Shahad; Jabbar Mnati, Mohannad; Ali Tofigh, Mohammad (International Journal of Engineering and Technology, 2018)
This paper discusses various passive filter designs to reduce the harmonic in the industrial distributions system. The passive filter used is a single and double tuned harmonic filter. In the designing of this filter, analyzing filter properties of passive component of the filter. The study was conducted to examine the efficacy of using single and double tuned filters in reducing harmonic as well as determining the best location to install the filters. Different system effects and load limits on harmonic distortion and performance of filters are also being examined. The output of the simulation indicated that a superior performance in extenuating harmonics by the double tuned filter is more effective in reducing harmonics when it is placed near the harmonic generating loads.